Apoptosis-associated speck-like protein containing a CARD regulates the growth of pancreatic ductal adenocarcinoma - Mitsuhito Koizumi (Nature Portfolio, 2021)
Abstract Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is a key adaptor protein of inflammasomes and a proapoptotic molecule; however, its roles in signal transduction in pancreatic ductal adenocarcinoma (PDAC) cells remain unknown. Here, we clarified the role and mechanisms of action of ASC in PDAC using clinical evidence and in vitro data. ASC expression in PDAC tissues was analyzed using public tumor datasets and immunohistochemistry results of patients who underwent surgery, and PDAC prognosis was investigated using the Kaplan–Meier Plotter. ASC expression in PDAC cells was downregulated using small-interfering RNA, and gene expression was assessed by RNA sequencing. Review of the Oncomine database and immunostaining of surgically removed tissues revealed elevated ASC expression in PDAC tumors relative to non-tumor tissue, indicating poor prognosis. We observed high ASC expression in multiple PDAC cells, with ASC silencing subsequently inhibiting PDAC cell growth and altering the expression of cell cycle-related genes. Specifically, ASC silencing reduced cyclin D1 levels and stopped the cell cycle at the G1 phase but did not modulate the expression of any apoptosis-related molecules. These results show that ASC inhibited tumor progression via cell cycle modulation in PDAC cells and could be a potential therapeutic target.